The Development of Internal Frame for Ceiling based on VAK Learning Model - mohamed, maziana; awang minggu, dayang najihah (Research and Innovation in Technical and Vocational Education and Training, 2021)
Teaching kit are one of the teaching aid that can be used by both teachers and students to facilitate learning especially in understanding technical subjects that need extensive imagination and ability to relate theory with practise. This teaching kit contains model material and equipment that can be used in practical works but with smaller scale where it can be mantle and dismantle of the internal frames of ceiling based on Visual, Audio, and Kinaesthetic   learning model. Therefore, this study is to  design and develop the teaching kit of internal frame for ceiling based on VAK learning model. This study is also conducted to evaluate the functionability of internal frame for ceiling in the teaching and learning process. Three selected experts will evaluate the internal frame of ceiling.  The instrument used was a set of questionnaire where it consists of 16 questions. The questions were divided into 4 sections, namely Part A - respondent’s information, Part B - the design of internal frame for ceiling, Part C - the functionability of internal frame for ceiling in the teaching and learning process, and Part D - comments and suggestions.    The collected data were analysed by using descriptive statistics method. Overall, the design of the internal frame of ceiling cater the VAK learning model and can be applied during teaching and learning process.